Hubungan Pengetahuan Ibu tentang Buku Kesehatan Ibu dan Anak (Kia) dengan Kejadian Stunting pada Balita di Desa Kuapan Wilayah Kerja UPT Puskesmas Tambang - Ariyanti, Dewi; Harahap, Dewi Anggriani; Dhilon, Dhini Anggraini (Evidence Midwifery Journal, 2024)
Mothers who have low knowledge about MCH tend not to realize if their children have nutritional disorders. The purpose of this study was to determine the relationship between mothers' knowledge of the Maternal and Child Health (MCH) book with the incidence of stunting in the working area of Puskesmas Tambang in 2023. This type of research is quantitative with a Cross Sectional design. The sample in this study were mothers of toddlers aged 24-60 months in Kuapan village in the working area of Puskesmas Tambang in 2023 as many as 194 people with the sampling technique was simple random sampling of 131 people. Data collection tools using questionnaires, weight measurement, height using microtoice. The results of univariate analysis showed that respondents had good knowledge about the MCH book as many as 104 people (79.4%), and did not experience stunting as many as 109 toddlers (83.2). The results of bivariate analysis on the relationship between maternal knowledge of the KIA book with the Chi Square test showed that there was a relationship between knowledge of the KIA book (p=0.00) with the incidence of stunting. In conclusion, there is a relationship between knowledge about the kia book and the incidence of stunting in toddlers in Kuapan Village in the working area of Puskesmas Tambang, Kampar Regency. It is expected that mothers of toddlers can increase the frequency of visiting the posyandu or puskesmas in order to get complete information from midwives and mothers can increase knowledge about the KIA book so that they can understand child growth and development.